Trophic state and growth parameters of Labiobarbus festivus and Osteochilus hasseltii at the Tekak River of Kenyir Lake, Malaysia - Ahmad Fathi bin Mohd Salleh (Kulliyyah of Science, International Islamic University Malaysia, 2018)
Studies on fish growth, condition, and spawning season and nutrient dynamics are important to evaluate a lake ecosystem. However, there are not adequate information on temporal nutrient dynamics, growth, condition, and spawning season of fishes in all rivers of Kenyir Lake. During this study, Labiobarbus festivus and Osteochillus hasseltii were selected to determine the growth, condition, and spawning season of fish as they are popular and important food fishes in Kenyir Lake and their captured production is gradually decreasing. In these contexts, a study was conducted on a prospective Tekak river of Kenyir Lake from Jan - Dec 2016 to (1) determine the spatio-temporal nutrient dynamics and trophic status of Tekak river, (2) investigate growth, condition and spawning season of fish, and (3) evaluate the growth parameters and spawning of L. festivus and O. hasseltii. Water quality and nutrient dynamics were studied in three sampling zones (downstream, middle and upstream) in the Tekak river. Each sampling zone was subdivided into three sampling sites. A series of water quality parameters and trophic status were determined monthly in each sampling site. All water quality parameters significantly changed over time and in all sampling zones (except total suspended solid and water transparency) were statistically similar. Both total suspended solid and transparency decreased from upstream to downstream. A significant negative correlation (r=-0.29, p<0.01) was observed between chlorophyll-a and temperature. Trophic state significantly changed over time. It indicates that the water of the sampling area from Tekak River of Kenyir Lake was oligotrophic (low productivity) with low nutrient concentrations. To estimate growth, condition and spawning season of fishes, monthly L. festivus and O. Hasseltii samples were collected using gill-net for a period of one year (Jan – Dec 2016). A total of 2126 (male: 771, female: 1355) L. festivus and 579 (male: 239, female: 340) O. hasseltii specimens were studied in this research. A negative allometric growth (b<3.0) of L. festivus was observed from February until June, and September for female while in January, March until June, and November for male L. festivus. Positive allometric growth (b>3.0) was observed in the remaining month of both male and female L. festivus. Male O. hasseltii, showed a negative allometric growth (b<3.0) in March and April, and a positive allometric growth (b>3.0) in January, March, August, October and November. Female O. hasseltii showed positive allometric growth (b>3.0) in all months except January, April, and July. Overall higher mean condition factor was observed in smaller compared to larger fish of both sexes. Both fishes showed spawning season from Sep-Feb with the peak of spawning for L. festivus was in November and December and for O. hasseltii the peak of spawning was in October and November (Female) and August (Male). The results of this study are useful for regular ecological monitoring and conservation of the lake. In this case, a careful monitoring is highly recommended to prevent spreading of unwanted materials in this lake. However, it can be concluded that the outcome of this study can be applied by the relevant lake authorities for the sustainable development of food fishes and endangered fishes in Kenyir Lake.